Seeking Grace in the Chasm:: Bridging Beauty and Virtue Theologically and Pastorally - Heeder, Megan (Lumen et Vita, 2020)
A hermeneutic of unity between beauty and virtue, inspired by the work of Gregory of Nazianzus, offers a way to seek the Holy Spirit’s presence in the apparent chasm between the church and the secular realm. This paper describes beauty’s role in Gregory of Nazianzus’ poetry and orations and analyzes how adopting Gregory’s hermeneutic of unity between beauty and virtue can strengthen the church’s relationship with the secular sphere. The paper’s second part draws on Karl Rahner’s conception of the anonymous Christian to detail how a willingness to recognize virtue’s beauty in the public sphere can open the ecclesial community to the Holy Spirit’s movement both within and beyond the church.